2011
DOI: 10.1111/j.1468-0416.2011.00169.x
|View full text |Cite
|
Sign up to set email alerts
|

The Choice and Role of Lockups in IPOs: Evidence from Heterogeneous Lockup Agreements

Abstract: This paper analyses heterogeneous lockup agreements from the London Stock Market. With hand-collected data, I compare and contrast absolute-date lockups with the relativedate lockups and single lockups versus staggered lockups. This paper tests several potential explanations for the choice of lockup contracts: (i) information asymmetry, (ii) signaling, (iii) agency problem, and (iv) certification. I find strong evidence for information asymmetry and certification (VC and prestigious underwriters) and partial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Third, lockups for LSE IPOs are quite diverse and heterogeneous particularly in terms of their length. For example, Espenlaub et al (2001) report average lockup length of 561 days whilst Hoque (2011) reports variation from 383 to 714 days for UK IPOs. This is in sharp contrast to the US findings of standardised lockups of 180 days (Field and Hanka, 2001;Brav and Gompers, 2003;Brau et al, 2004;Yung and Zender, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, lockups for LSE IPOs are quite diverse and heterogeneous particularly in terms of their length. For example, Espenlaub et al (2001) report average lockup length of 561 days whilst Hoque (2011) reports variation from 383 to 714 days for UK IPOs. This is in sharp contrast to the US findings of standardised lockups of 180 days (Field and Hanka, 2001;Brav and Gompers, 2003;Brau et al, 2004;Yung and Zender, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Lockups prevent firms’ insiders from selling whole or some percentage of their equity during post‐IPO periods. Existing literature shows that the majority of US and UK firms go public with voluntary lockups (Espenlaub et al., ; Field and Hanka, ; Mohan and Chen, ; Hoque, ) and tends to focus on roles of lockups and their price effect around expiry dates (Brav and Gompers, ; Brau et al., ; Arthurs et al., ; Yung and Zender, ). Although IPOs’ survival has been studied before (Jain and Kini, , ), the association of the survival and characteristics of lockups has not received attention in the past .…”
Section: Introductionmentioning
confidence: 99%
“…In this case, establishing more extended lock-up periods represents a sign of management's commitment to offset the high moral hazard. Hoque (2011) investigated potential explanations for choosing the type of lock-up contract in IPOs in the United Kingdom, where the extension of the lock-up term has a heterogeneous distribution, ranging from 85 days to 1,650 days. Among his results, he found that the presence of venture capital funds and prestigious underwriters confer a kind of certification on the firm's quality, allowing for more flexible and less restricted lock-up contracts, corroborating the results found by Brav and Gompers (2003).…”
Section: Theoretical Background and Formulation Of Hypothesesmentioning
confidence: 99%
“…Evidence of the impact of lock-up expiration differs in terms of magnitude and signal in different countries. Hoque (2011) 2012) investigated the lockup phenomenon in the Middle East and North Africa (MENA). They found that the greater the length of the lock-up period, the greater the price drop, and that this price drop is sharp for family businesses.…”
Section: Theoretical Background and Formulation Of Hypothesesmentioning
confidence: 99%
“…Nonetheless, the lock-ups have varied periods (Espenlaub et al, 2001;Goergen et al, 2006;Ahmad and Jelic, 2014), and the short-and long-term information disclosures will result in multiple transparency levels because negative information is typically only disclosed in the long term. Hence, more stringent and longer lock-ups are needed to ensure higher degrees of information asymmetry so that greater disclosure is possible (Goergen et al, 2006;Hoque, 2011). A similar condition applies to offer price.…”
Section: Literature Reviewmentioning
confidence: 99%